2013
DOI: 10.1007/s12098-013-1097-5
|View full text |Cite
|
Sign up to set email alerts
|

ADad 3: The Epidemiology of Anxiety Disorders Among Adolescents in a Rural Community Population in India

Abstract: The prevalence of Anxiety Disorders in South Indian adolescents was higher than found in the western literature. Prevalence of specific AD was age and gender specific. Adolescent and mental health policies must integrate anxiety disorder of public health significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 29 publications
3
25
0
Order By: Relevance
“…[2] The prevalence was higher among females than males in this study which is similar to the findings of the other studies with a range of 9.6-16.5%. [1,4,7] The incidence of social anxiety in the sample of the population of school going children under the age group 14-17 years to be 10.3% by liebowitz social anxiety scale. [4] The age distribution clearly showed that the level of social anxiety was higher in children in their early teens, standing at 11.9% in 14 years old, 17.0% in 15 years, 6.4% in 16 years, and 0% in 17 years old children (P < 0.05) and similar observation was found in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] The prevalence was higher among females than males in this study which is similar to the findings of the other studies with a range of 9.6-16.5%. [1,4,7] The incidence of social anxiety in the sample of the population of school going children under the age group 14-17 years to be 10.3% by liebowitz social anxiety scale. [4] The age distribution clearly showed that the level of social anxiety was higher in children in their early teens, standing at 11.9% in 14 years old, 17.0% in 15 years, 6.4% in 16 years, and 0% in 17 years old children (P < 0.05) and similar observation was found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…This community-based, cross-sectional, and descriptive study was conducted in the month of August 2016 among the school children studying [6][7][8][9][10] th standard from randomly selected six schools in Sathanur, Hobli of Ramnagara district. The schools were three government and three privately owned.…”
Section: Methodsmentioning
confidence: 99%
“…Epidemiological studies across the world have reported the prevalence of anxiety disorder ranging from 2 to 24% with the median prevalence rate of 8% [35]. Epidemiological studies from India report a prevalence ranging from 4 to 14.4% [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Comparably, in India, a meta-analysis of 13 psychiatric epidemiological studies (N=33,572) conducted in urban and rural India across all age groups yielded an estimated prevalence rate of 5.8% for GAD [ 4 ]. Similarly, Nair et al [ 5 ] found a 6.6% prevalence of GAD among adolescents in India. In Indian universities, in particular, Sahoo and Khess [ 6 ] found a 19% prevalence of GAD in 405 young male university students.…”
Section: Introductionmentioning
confidence: 90%
“…These studies suggest that anxiety is a major public health concern, particularly in Indian students. Given that the global average age of onset of GAD is in adolescence and in early adulthood [ 1 , 5 , 7 , 8 ], university students are a vulnerable population.…”
Section: Introductionmentioning
confidence: 99%